Implementasi Pembelajaran Berdiferensiasi di Sentra Persiapan pada Pendidikan Anak Usia Dini - Maiyida Safita; Penia Lisa Ogemi (Educalia: Journal of Educational Research, 2026)
This study aims to examine the implementation of differentiated learning in early childhood preparation centers as an effort to create learning that is appropriate to the individual developmental needs of students. Differentiated learning is a learning approach that provides services according to the needs, interests, readiness, and learning styles of children. This study discusses the implementation of differentiated learning in early childhood preparation centers. Using descriptive qualitative methods, data were collected through observation, interviews, and documentation. The results showed that teachers implemented differentiated learning by adjusting the content, process, and learning products. The strategies used included flexible grouping, providing activity options, and using a variety of media according to children's characteristics. This implementation had a positive impact on learning motivation, children's engagement, and early literacy development. Thus, differentiated learning has proven relevant in supporting meaningful learning in early childhood preparation centers. Abstrak Penelitian ini bertujuan untuk mengkaji implementasi pembelajaran berdiferensiasi di sentra persiapan pada anak usia dini sebagai upaya menciptakan pembelajaran yang sesuai dengan kebutuhan perkembangan individu peserta didik. Pembelajaran berdiferensiasi merupakan pendekatan pembelajaran yang memberikan layanan sesuai dengan kebutuhan, minat, kesiapan, dan gaya belajar anak. Penelitian ini membahas implementasi pembelajaran berdiferensiasi di sentra persiapan pada satuan pendidikan anak usia dini. Melalui metode kualitatif deskriptif, data dikumpulkan menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru telah menerapkan pembelajaran berdiferensiasi melalui penyesuaian konten, proses, dan produk pembelajaran. Strategi yang digunakan meliputi pengelompokan fleksibel, penyediaan pilihan aktivitas, dan penggunaan media yang bervariasi sesuai karakteristik anak. Implementasi ini berdampak positif terhadap motivasi belajar, keterlibatan anak, serta perkembangan literasi awal. Dengan demikian, pembelajaran berdiferensiasi terbukti relevan dalam mendukung pembelajaran bermakna di sentra persiapan pada anak usia dini.